Autopoiesis of Psychoanalytic Subject - DAIKOUJI, Kouhei (Japanese Sociological Review, 2001)
This article represents an attempt to define the proper position of Jacques Lacan's psychoanalytic theory in mind theory. To this end, Lacan's theory of discourse is reviewed and examined in relation to Niklas Luhmann's theory of autopoietic systems. Lacan assumes the psyche of human beings operates in a completely different way from the mind of animals. However we emphasize that there may be common aspects between human and other animals. So I adopt an alternative approach presuming the duality of human beings, that is, their “subject-of-speech” and “being-as-animal” qualities. At the same time, I demonstrate some theoretical difficulties posed by that duality. Two characteristics, extracted from Lacan's writings, are shown to have something in common with Luhmann's theory. The first one is the concept of “structure”. It is oriented to the relationship between system and its environment. The second is the mechanism of “detautologization” through which the system utilizes disturbances of its environment. As a result, I present the possibility that the relation between “subject-of-speech” and “being-as-animal” qualities can be theorized properly as structural coupling.